The timing of strike-slip shear along the Ranong and Khlong Marui faults, Thailand - Watkinson, I.; Elders, C.; Batt, G.; Jourdan, Fred; Hall, R.; McNaughton, Neal (American Geophysical Union, 2011)
The timing of shear along many important strike-slip faults in Southeast Asia, such as the Ailao Shan-Red River, Mae Ping and Three Pagodas faults, is poorly understood. We present 40Ar/39Ar, U-Pb SHRIMP and microstructural data from the Ranong and Khlong Marui faults of Thailand to show that they experienced a major period of ductile dextral shear during the middle Eocene (48–40 Ma, centered on 44 Ma) which followed two phases of dextral shear along the Ranong Fault, before the Late Cretaceous (>81 Ma) and between the late Paleocene and early Eocene (59–49 Ma). Many of the sheared rocks were part of a pre-kinematic crystalline basement complex, which partially melted and was intruded by Late Cretaceous (81–71 Ma) and early Eocene (48 Ma) tin-bearing granites. Middle Eocene dextral shear at temperatures of ~300–500°C formed extensive mylonite belts through these rocks and was synchronous with granitoid vein emplacement. Dextral shear along the Ranong and Khlong Marui faults occurred at the same time as sinistral shear along the Mae Ping and Three Pagodas faults of northern Thailand, a result of India-Burma coupling in advance of India-Asia collision. In the late Eocene (<37 Ma) the Ranong and Khlong Marui faults were reactivated as curved sinistral branches of the Mae Ping and Three Pagodas faults, which were accommodating lateral extrusion during India-Asia collision and Himalayan orogenesis.